KEWENANGAN DISKRESI DAN PERTANGGUNGJAWABAN HUKUM DALAM PELAKSANAAN TUGAS DAN FUNGSI KEPOLISIAN - Ariakta Gagah Nugraha; Umar Ma’ruf (UNISSULA Semarang, 2018)
This research entitled Authority of Discretion and Legal Liability in the Implementation of Duties and Functions of the Police. The purpose of this study: 1) To know and analyze the need to do the discretion in the police. 2) To know and analyze what are the authority of police discretion in Polres Pekalongan City. 3) To know and analyze discretionary legal accountability applied in the execution of duties and functions of police in Polres Pekalongan City.Result of research: 1) Legal basis of Police Discretion among others is Law Number 2 Year 2002 Article 18 paragraph (1). 2) Police Discretion in its implementation need to know the Ethics of Police Profession, 3) Application of Discretion that can not be prosecuted before the law is Discretion Action which is limited by: a. Principle of need, b. Actions that are really for the sake of police duty. c. Destination principle, .d. The principle of balance. Keywords: Discretionary Authority, Implementation of Duties and Functions of the Police